Effect of soil amendments on radiocesium transfer to alfalfa - Ioannides, K.G.; Papachristodoulou, C.A.; Mertzimekis, T. J.; Tzialla, C.E. (Health Phys., 2003)
Greenhouse experiments were carried out to evaluate the effect of different soil-based countermeasures on radiocesium transfer to Medicago sativa (alfalfa) grown on artificially contaminated loamy-clayey soil. Various rates of potassium, ammonium, and Prussian Blue supplements were applied, and the uptake of radiocesium by control and treated alfalfa plants was monitored during four growth periods. Transfer factors ranging between 0.06 and 0.02 were determined for control plants. Application of potassium at rates higher than 0.1 meq per 100 g soil was found to suppress radiocesium uptake, the effect being more pronounced at increasing fertilization rates. On the contrary, soil treatment with ammonium enhanced the bio-accumulation of radiocesium, indicating that Cs+ ions, previously unavailable to plant roots, were released from soil particles. Prussian Blue supplements had practically no effect on soil-to-alfalfa transfer of the radionuclide.
Keywords: 137Cs; Accidents; Agriculture; alfalfa; ammonia; article; bioaccumulation; Biological Availability; cesium; cesium 137; Cesium Radioisotopes; Computer-Assisted; Contamination; controlled study; environmental; ferric ferrocyanide; Ferrocyanides; Food chain; Food Contamination; Medicago; Medicago sativa; nonhuman; nuclear; nuclear accident; plant root; Plant Roots; potassium; priority journal; Quaternary Ammonium Compounds; radiation monitoring; Radioactive; radioactive contamination; Radiotherapy Planning; Reference Values; Reproducibility of Results; Sensitivity and Specificity; soil amendment; soil fertilization; Soil Pollutants